2022
DOI: 10.1177/02692163221133665
|View full text |Cite
|
Sign up to set email alerts
|

‘Sadly I think we are sort of still quite white, middle-class really’ – Inequities in access to bereavement support: Findings from a mixed methods study

Abstract: Background: Voluntary and community sector bereavement services are central to bereavement support in the UK. Aim: To determine service providers’ perspectives on access to their support before and during the COVID-19 pandemic. Design: Mixed methods study using an explanatory sequential design: (1) Cross-sectional online survey of UK bereavement services; (2) Qualitative interviews with staff and volunteers at selected services. Settings/participants: 147 services participated in the survey; 24 interviews were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Several of these studies have also investigated the effects of demographic and other known risk factors for adverse grief and health outcomes. Consistent with pandemic ( 12 14 , 28 , 29 ) and non-pandemic research ( 9 , 30 ), our baseline results identified relationship with the deceased as the strongest factor predicting grief vulnerability ( 23 ). Younger age of the deceased was also associated with worse baseline grief vulnerability ( 23 ), as in other studies ( 9 , 29 , 31 ).…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Several of these studies have also investigated the effects of demographic and other known risk factors for adverse grief and health outcomes. Consistent with pandemic ( 12 14 , 28 , 29 ) and non-pandemic research ( 9 , 30 ), our baseline results identified relationship with the deceased as the strongest factor predicting grief vulnerability ( 23 ). Younger age of the deceased was also associated with worse baseline grief vulnerability ( 23 ), as in other studies ( 9 , 29 , 31 ).…”
Section: Introductionsupporting
confidence: 79%
“…Despite the disproportionate impacts of the pandemic on minoritized ethnic communities, in terms of death-rates, and disruption to grieving practices and community networks ( 28 , 78 ), this group of participants actually had better levels of PGD symptoms (but not grief vulnerability), although the difference was not statistically significant in the mixed-model. Further, the small size of this group (particularly at later time points) and the lessened effect of ethnicity once other factors were controlled, means that this finding should be treated cautiously.…”
Section: Discussionmentioning
confidence: 90%
“…The study reported a concerning disparity in access to services for ethnic minority groups before and throughout the COVID‐19 pandemic in the UK. The study highlights the need to improve culturally sensitive bereavement services for ethnic minorities (Selman et al, 2022).…”
Section: Discussionmentioning
confidence: 95%
“…(Torrens‐Burton et al, 2022). Moreover, Selman et al (2022) conducted research on the accessibility of bereavement services from the service providers' perspective using a cross‐sectional survey and interviews. The study reported a concerning disparity in access to services for ethnic minority groups before and throughout the COVID‐19 pandemic in the UK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation